(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
This paper gives the concept of personnel costs and personnel optimization. The peculiarities of personnel cost planning are considered and the main factors influencing planning are listed. Indicators and approaches to optimizing personnel costs are also described.